2012
DOI: 10.1088/0029-5515/52/12/123016
|View full text |Cite
|
Sign up to set email alerts
|

Statistical features of coherent structures at increasing magnetic field pitch investigated using fast imaging in QUEST

Abstract: Fluctuations in slab plasma produced by electron cyclotron waves in an open magnetic configuration with vertical (B z ) and toroidal (B t) fields are investigated as a function of B z /B t (field pitch) using a high speed visible camera in the spherical tokamak QUEST. Higher order moments (skewness s and kurtosis k) of spatio-temporal fluctuations are investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 43 publications
5
36
0
Order By: Relevance
“…However, it has been shown that, at similar n e and T e in TORPEX as compared to our experiment, the mean value of the light emission signal recorded with a tangential fast camera depends linearly on n e at varying neutral hydrogen density. 6,16 Hence, in our case too, it is reasonable to interpret that the intensity fluctuations resembles the density fluctuations to an appreciable extent.…”
Section: Turbulent Velocity Field Estimationsupporting
confidence: 65%
See 1 more Smart Citation
“…However, it has been shown that, at similar n e and T e in TORPEX as compared to our experiment, the mean value of the light emission signal recorded with a tangential fast camera depends linearly on n e at varying neutral hydrogen density. 6,16 Hence, in our case too, it is reasonable to interpret that the intensity fluctuations resembles the density fluctuations to an appreciable extent.…”
Section: Turbulent Velocity Field Estimationsupporting
confidence: 65%
“…With the advent of density fluctuation diagnostics with high spatial and temporal resolutions, quantitative analysis of such velocities and derived quantities like Reynolds stress and zonal flows becomes feasible. Turbulence imaging diagnostics have been realized in several forms like the beam emission spectroscopy (BES), 2 fast visible imaging, [3][4][5][6] and microwave reflectometer imaging array. 7,8 Particle Image Velocimetry (PIV) has proven to be an important tool for quantitative estimation of two-dimensional flow structures in experimental fluid mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…27 Tangential passive imaging of visible light (mainly Hα) was also done in the Q-shu University Experiment with Steady State Spherical Tokamak (QUEST) device in a simple torus configuration, showing blob formation and propagation similar to that in a tokamak SOL. 28 High speed camera imaging of neutral hydrogen recycling near a limiter was done in the TJ-II stellarator, and the 2-D motion of plasma blobs was observed within the shear layer. 29,30 High speed imaging was also done in the TJ-K stellarator using tangential viewing without filters, but with a small depth of field to minimize the effects due to integration along the line of sight.…”
Section: Passive Turbulence Imaging Without a Gas Puffmentioning
confidence: 99%
“…A quantitative evaluation of this effect is carried out under the framework of the TITR code [5,11]. It is seen that the effect is negligible in the edge and SOL of the plasma as compared to the plasma core as the density and hence the intensity is appreciably smaller in that region.…”
Section: Turbulent Velocity Field Estimationmentioning
confidence: 99%
“…becomes feasible. Turbulence imaging diagnostics have been realized in several forms like the beam emission spectroscopy (BES) [1], fast visible imaging [2][3][4][5] and microwave reflectometer imaging array [6,7].…”
Section: Introductionmentioning
confidence: 99%